2004
DOI: 10.1002/jsfa.1849
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds and the colour of oranges subjected to a combination treatment of waxing and irradiation

Abstract: The effects of waxing, irradiation doses and storage on phenolic compounds and colour of irradiated oranges were investigated. Mature oranges (Citrus sinensis (L) Osbeck var Maroc late) waxed or unwaxed were treated with 0, 1 or 2 kGy radiation and stored up to 9 weeks at 20 • C and 40-50% RH. Colour of the oranges, total phenols and flavones in the peel were measured. Phenolic compounds increased with irradiation dose and storage time. Hue angle, L * value and chroma of the orange colour were more affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Phenolics are secondary metabolites produced by the plant, and its increased biosynthesis is a typical reaction of plant tissue to irradiation and other stress factors (). Increases in the concentration of phenolics due to irradiation have been attributed to enhanced phenylalanine ammonia−lyase (PAL) activity ( , ). PAL (EC 4.3.1.5) catalyzes the first connected step in the biosynthesis of a diverse range of phenyl proponoid derived secondary products in plants such as flavonoids, isoflavonoids, coumarins, and lignins ().…”
Section: Resultsmentioning
confidence: 99%
“…Phenolics are secondary metabolites produced by the plant, and its increased biosynthesis is a typical reaction of plant tissue to irradiation and other stress factors (). Increases in the concentration of phenolics due to irradiation have been attributed to enhanced phenylalanine ammonia−lyase (PAL) activity ( , ). PAL (EC 4.3.1.5) catalyzes the first connected step in the biosynthesis of a diverse range of phenyl proponoid derived secondary products in plants such as flavonoids, isoflavonoids, coumarins, and lignins ().…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoids are divided into two groups: carotene and xanthophyll. The yellow color found in fruit and vegetables is a result of the loss of chlorophyll with the ripening of fruit and the carotenoids becoming more visible (Moussaid et al, 2000). The consequences of different gamma radiation doses on the color parameters of orange peels and juices are determined and presented in Table 4.…”
Section: Total Carotenoids (Tc)mentioning
confidence: 99%
“…Color development, particularly carotenoid synthesis, was probably adversely affected due to irradiation in oranges (Ladaniya et al, 2003). Moussaid et al (2000) explained that irradiation affected h (hue angle) value and C (chroma, color intensity) values more than other parameters in waxed oranges. Although irradiation also affects L (lightness), it does not affect a (redness) and C (color intensity).…”
Section: Total Carotenoids (Tc)mentioning
confidence: 99%
“…The redness of orange peel decreases, and the yellowness increases as the concentration of the phenolic compounds becoming more dominant. Ionizing irradiation and storage increased concentration of the total phenols, and therefore the color of orange peel became more yellowish [ 6 ]. The paper suggested that scutellarein was one of phenolic compounds in orange peel and was about 0.28 mg/g dried orange peel.…”
Section: Introductionmentioning
confidence: 99%